Analytical model and new structure of the enhancement-mode polarization-junction HEMT with vertical conduction channel. (April 2016) - Yang, Chao; Xiong, Jiayun; Wei, Jie; Wu, Junfeng; Peng, Fu; Deng, Siyu; Zhang, Bo; Luo, Xiaorong
Abstract: A novel enhancement-mode (E-mode) polarization-junction HEMT with vertical conduction channel (PVC-HEMT) is proposed, and its analytical model for threshold voltage ( V th ) is presented. It has two features: one is GaN/AlGaN/GaN double hetero-structure, the other is that source and drain locate at the same side of trench-type MOS gate (T-gate), and the source contacts with the T-gate, which forms vertical conduction channel (VC). The 2-D hole gas (2-DHG) and 2-D electron gas (2-DEG) are formed at the GaN-top/AlGaN and AlGaN/GaN-buffer interface, respectively, forming the polarization-junction. First, the E-mode operation is realized because 2-DHG under the source prevents the electrons injecting from source to 2-DEG, breaking through the conventional E-mode method by depleting 2-DEG under the gate. Second, a uniform electric field (E-field) distribution is achieved due to the assisted depletion effect by polarization-junction. Third, the source reduces the E-field peak at the T-gate side and modulates the E-field distribution. The breakdown voltage (BV) of PVC-HEMT is 705 V and specific ON-resistance ( R ON, sp ) is 1.18 mΩ cm 2 . Compared with conventional HEMT (C-HEMT), PVC-HEMT has a smaller size due to the special location of the source and T-gate. An analytic threshold voltage model is presented and the analytical results agree well with the simulated results. Highlights: A novel enhancement-mode (E-mode) polarization-junction HEMT with vertical conduction channel (PVC-HEMT) is proposed. A novel E-mode operation is realized because 2-DHG under the source prevents the electrons injecting from source to 2-DEG A uniform electric field (E-field) distribution is achieved due to the assisted depletion effect by polarization-junction. An analytic threshold voltage model is presented and the analytical results agree well with the simulated results. The device proposed a better trade-off relationship between breakdown voltage and specific on-resistance